(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2016)
The objective of this paper is to compare the rules of origin between the regionalintegration agreement Pacific Alliance and the Colombia free trade agreements withChile, CAN and G3, in order to determine if there are significant differences betweenthem. During this research, evidence shows that there are differences in the rules of originamong free trade agreements, this could generate incentives to the exporter in theposition of choosing a specific trade agreement. The main conclusion is that not always the best option to export to Chile, Mexico or Peruis through the Pacific Alliance, as would be expected to be the most recent agreement.The choice of agreement depends on the merchandise to be exported, so it isrecommended to look for the tariff subheading beforehand and to analyze which treatywould be most beneficial to export, according to its characteristics and composition.